2002
DOI: 10.1002/ppul.10015
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled study of in‐hospital exercise training programs in children with cystic fibrosis

Abstract: The aim of this study was to compare aerobic and resistance training in children with cystic fibrosis (CF) admitted to hospital with an intercurrent pulmonary infection with a control group. The subjects were randomized into three groups on the first day of admission. The fat-free mass (FFM) was calculated, using the skin fold thickness from four sites (biceps, triceps, subscapular, and iliac crest). Pulmonary function tests were performed within 36 hr of admission and repeated on discharge from the hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
257
6
14

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(289 citation statements)
references
References 21 publications
12
257
6
14
Order By: Relevance
“…Seven trials using randomised parallel-group design were included, with a total of 231 participants including children and adults. Three studies included children only (Selvadurai et al, 2002;Klijn et al, 2004;Turchetta et al, 2004), and two notable studies included adults and children (Cerny, 1989;Schneiderman-Walker et al, 2000). Overall, these trials showed some evidence of benefits of short-and long-term physical training for people with CF, and this was also the conclusion provided by other reviews in the field (Smidt et al, 2005;Bradley et al, 2006;Shoemaker and Hurt, 2008).…”
Section: Benefits Of Exercise For People With Cystic Fibrosissupporting
confidence: 51%
See 2 more Smart Citations
“…Seven trials using randomised parallel-group design were included, with a total of 231 participants including children and adults. Three studies included children only (Selvadurai et al, 2002;Klijn et al, 2004;Turchetta et al, 2004), and two notable studies included adults and children (Cerny, 1989;Schneiderman-Walker et al, 2000). Overall, these trials showed some evidence of benefits of short-and long-term physical training for people with CF, and this was also the conclusion provided by other reviews in the field (Smidt et al, 2005;Bradley et al, 2006;Shoemaker and Hurt, 2008).…”
Section: Benefits Of Exercise For People With Cystic Fibrosissupporting
confidence: 51%
“…Importantly, participation in regular physical activity is associated with many holistic benefits, such as improved quality of life and wellbeing (Boas, Danduran, & McColley, 1999;Orenstein, Nixon, Ross, & Kaplan, 1989;Selvadurai et al, 2002). The ICF-CY model facilitates exploration of the impact of exercise intervention on these wider aspects of functioning.…”
Section: Benefits Of Exercise For People With Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that significant differences have been reported in LBM between athletes and nonathletes (35), changes following exercise (14 -16), and longitudinal studies or exercise training studies of special populations (e.g., cystic fibrosis, Prader-Willi syndrome, etc.) (28,42,44,50). However, few studies have examined the influence of free-living, habitual PA on LBM accrual during adolescence, a critical period of growth affecting body composition and those that have, for the most part, been cross-sectional in design and thus unable to tease out the independent effects of PA from those of growth and maturation (12,21,25).…”
mentioning
confidence: 99%
“…If exercise training including anaerobic exercises can improve muscle strength and muscle size resulting in weight gain remains also under consideration. Further, in terms of quality of life, positive effects towards perceived feasibility have been noted (Turchetta eta l., 2004, Selvadurai et al, 2002, Schneiderman-Walker et al, 2000, Orenstein et al, 1981.…”
Section: Perspectives In Clinical Practice: Rehabilitation Programsmentioning
confidence: 99%